Pelatihan Pembibitan dan Pembuatan Produk Minuman Jahe Bagi Kelompok Wanita Tani (KWT) “Dewi Sri” Desa Kemetul Kecamatan Susukan - Wahyudi, Avian Tri; Prasetyo, Damar Adi; Vifta, Rissa Laila; Pujiastuti, Anasthasia; Santoso, Wingit (UNIVERSITAS NGUDI WALUYO, 2021)
Ginger is a one of rhizome herbal plant that has many health benefits. Consumption of ginger both directly and through the manufacture of ginger-based products has also increased during the pandemic and after the pandemic. The utilization of yard land that is less than optimal and the low selling of ginger are the main problems faced by the Women Farmer Group